Buildings as non‐human narrators: Between post‐phenomenological and object‐oriented architectural geographies. Issue 3 (17th May 2021) - Rossetto, Tania; Peterle, Giada
Abstract : This paper intervenes in the current debate on architectural geography and the lives of buildings, aiming to provide some suggestions in light of the recent development of post‐phenomenological and object‐oriented geographical theorisation. Despite the fact that new non‐representational approaches in architectural geography do pay attention to the materialities and agencies of non‐human actors, we argue that such readings often tend to remain phenomenological and human‐centred and fail to experiment more radically with a post‐phenomenological, object‐centred stance. Analysing an example of filmic it‐narration by a fictional speaking building, namely Wim Wenders' The Berlin Philharmonic (2014), we situate the device of non‐human narration as an experimental field for advancing a critical reflection on geographic epistemologies. Critically analysed in its paradoxes and oscillations, with its double dialectic of both empathy and defamiliarisation, it‐narration provides new insights into architectural geographies by enacting a post‐phenomenology that is consciously and aesthetically object‐oriented. We take both architectural geography and narratology as a testing ground to show the possibilities of expanding such conceptualisation within a broader range of geographical subfields. Abstract : Analysing an example of filmic it‐narration by a fictional speaking building, namely Wim Wenders' The Berlin Philharmonic (2014), we situate the narrative device of non‐human narration as an experimental field for advancing a critical reflection on geographic epistemologies.